2016
DOI: 10.9745/ghsp-d-15-00327
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Access to a New, More Affordable Levonorgestrel Intrauterine System in Kenya: Service Delivery Costs Compared With Other Contraceptive Methods and Perspectives of Key Opinion Leaders

Abstract: At a public-sector transfer price of US$15 per unit, the direct service delivery cost of Medicines360's levonorgestrel intrauterine system (LNG IUS) per couple-years of protection is comparable with the cost of other contraceptive products commonly procured in Kenya. Interviews with key opinion leaders suggest that introduction of a more affordable LNG IUS could help increase demand for the method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 14 publications
1
41
0
Order By: Relevance
“…Along with the improved low-dose ARVs themselves, the formulation or devices through which long-acting ARVs are delivered will be a critically important component influencing effectiveness, patient acceptability, deliverability, and cost of the ultimate products. Silicone matrix implants are widely used for contraceptive implants and cost less than US$10 for generic versions of an implant that is effective for 5 years 26 . But the daily doses required for long-acting hormonal contraception, which, after an initial burst phase, typically release doses of active agents of 50 micrograms or less per day, 27 is about 2 orders of magnitude less than the daily amount to be released from the current long-acting nanoemulsion of cabotegravir.…”
Section: Implants That Are Easier To Implement: Biodegradable and Refmentioning
confidence: 99%
“…Along with the improved low-dose ARVs themselves, the formulation or devices through which long-acting ARVs are delivered will be a critically important component influencing effectiveness, patient acceptability, deliverability, and cost of the ultimate products. Silicone matrix implants are widely used for contraceptive implants and cost less than US$10 for generic versions of an implant that is effective for 5 years 26 . But the daily doses required for long-acting hormonal contraception, which, after an initial burst phase, typically release doses of active agents of 50 micrograms or less per day, 27 is about 2 orders of magnitude less than the daily amount to be released from the current long-acting nanoemulsion of cabotegravir.…”
Section: Implants That Are Easier To Implement: Biodegradable and Refmentioning
confidence: 99%
“…A total of 1009 citations were screened from which 20 papers were suitable for inclusion. Of these, 11 reported research undertaken in the USA, five in the UK and one each in Iran, Kenya, Norway and Sweden . Fourteen studies reported the results of economic models, five were based on observational cohort studies and one was a health technology assessment.…”
Section: Resultsmentioning
confidence: 99%
“…(1995), the number of pregnancies avoided was reported graphically only, so it was not possible to extract the outcomes data . In two other studies, effectiveness outcomes were reported as couple years of protection, making comparisons between studies more difficult . The remaining two studies reported outcomes on the basis of quality‐adjusted life years (QALYs) gained, a metric which combines the effect of contraception on women's quality of life with overall survival …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed that nurse-midwives would provide implant insertions and removals, 9 and labor costs were calculated using labor times from Avenir Heath's OneHealth Tool 10 and public-sector staff's average salary information in Kenya 3 . Based on our estimates, more than 22,747 staff hours/week, or 569 full-time equivalents (FTEs), will be required to provide these 4.5 million removals, with nearly 14,500 hours/week (363 FTEs) required in Ethiopia and Tanzania alone (for the more detailed analysis, see the Supplement).…”
mentioning
confidence: 99%